Effects of Drought Stress on the Growth and Physiological Characteristics of Idesia polycarpa Maxim - Xiaoyu Lu; Yian Yin; Maolin Yang; Shucheng Zhang; Zhangtai Niu; Lingli Wu; Chan Chen (Horticulturae, 2025)
Idesia polycarpa is a valuable woody oil plant with potential for horticultural and industrial applications. However, limited information is available regarding its drought tolerance during the seedling stage. In this study, one-year-old seedlings were subjected to five treatments based on soil relative water content (RWC): moderate drought (T1, 40 ± 5%), severe drought (T2, 20 ± 5%), control (CK, 70 ± 5%), and rewatering following moderate (T3) and severe drought stress (T4), with RWC restored to 70 ± 5%. Under drought stress, seedlings exhibited adaptive responses including reduced growth, enhanced antioxidant enzyme activity, osmotic regulation, and changes in endogenous hormone levels. Seedlings showed good tolerance and recovery under moderate drought, but severe drought caused substantial damage and limited post-rewatering recovery. Pearson correlation and principal component analyses revealed that betaine, APX, SA, IAA, ABA, chlorophyll (a + b) content, and crown growth were strongly associated with drought response and could serve as key indicators for drought resistance assessment in I. polycarpa. These findings provide insights into the physiological mechanisms of drought adaptation and support the development of a reliable evaluation system for drought tolerance in this promising species.